Effects of a nutritional intervention on impaired behavior and cognitive function in an emphysematous murine model of COPD with endotoxin-induced lung inflammation - Pelgrim, Charlotte E.; van Ark, Ingrid; van Berkum, Ronja E.; Schuitemaker-Borneman, Anne M.; Flier, Inge; Leusink-Muis, Thea; Janbazacyabar, Hamed; Diks, Mara A. P.; Gosker, Harry R.; Kelders, Marco C. J. M.; Langen, Ramon C. J.; Schols, Annemie M. W. J.; et al. (Frontiers in Nutrition, 2022)
One cluster of the extrapulmonary manifestations in chronic obstructive pulmonary disease (COPD) is related to the brain, which includes anxiety, depression and cognitive impairment. Brain-related comorbidities are related to worsening of symptoms and increased mortality in COPD patients. In this study, a murine model of COPD was used to examine the effects of emphysema and repetitive pulmonary inflammatory events on systemic inflammatory outcomes and brain function. In addition, the effect of a dietary intervention on brain-related parameters was assessed. Adult male C57Bl/6J mice were exposed to elastase or vehicle intratracheally (i.t.) once a week on three consecutive weeks. Two weeks after the final administration, mice were i.t. exposed to lipopolysaccharide (LPS) or vehicle for three times with a 10 day interval. A dietary intervention enriched with omega-3 PUFAs, prebiotic fibers, tryptophan and vitamin D was administered from the first LPS exposure onwards. Behavior and cognitive function, the degree of emphysema and both pulmonary and systemic inflammation as well as blood-brain barrier (BBB) integrity and neuroinflammation in the brain were assessed. A lower score in the cognitive test was observed in elastase-exposed mice. Mice exposed to elastase plus LPS showed less locomotion in the behavior test. The enriched diet seemed to reduce anxiety-like behavior over time and cognitive impairments associated with the presented COPD model, without affecting locomotion. In addition, the enriched diet restored the disbalance in splenic T-helper 1 (Th1) and Th2 cells. There was a trend towards recovering elastase plus LPS-induced decreased expression of occludin in brain microvessels, a measure of BBB integrity, as well as improving expression levels of kynurenine pathway markers in the brain by the enriched diet. The findings of this study demonstrate brain-associated comorbidities – including cognitive and behavioral impairments – in this murine model for COPD. Although no changes in lung parameters were observed, exposure to the specific enriched diet in this model appeared to improve systemic immune disbalance, BBB integrity and derailed kynurenine pathway which may lead to reduction of anxiety-like behavior and improved cognition.